The Influence of Product Quality, Price, and Promotion on Purchasing Decisions for Hybrid Chicken Eggs at CV Maju Jaya Karya Bersama in Ketapang Regency - Azhar Mahendra; Sukardi Sukardi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the factors influencing purchasing decisions for hybrid chicken eggs at CV Maju Jaya Karya Bersama in Ketapang Regency. The study focuses on three main factors: product quality, price, and promotion, and investigates how these elements affect consumer behavior. The primary objective of this research is to analyze whether these factors significantly influence purchasing decisions. Data were collected through a questionnaire distributed via Google Forms to 100 respondents selected using purposive sampling. The study employed multiple linear regression analysis with SPSS to assess the impact of each factor. The results indicate that product quality, price, and promotion simultaneously and partially affect purchasing decisions. Product quality has been shown to have a strong impact, as consumers are more likely to purchase eggs that meet their expectations regarding cleanliness, durability, and nutritional value. Price also plays an important role, with reasonable prices that align with the quality of the product helping to increase consumer interest. Promotion, especially direct marketing strategies, significantly influences consumer awareness and purchasing decisions. The findings suggest that CV Maju Jaya Karya Bersama should continue focusing on improving product quality, setting competitive prices, and implementing more creative promotional strategies to increase sales and customer loyalty.